2021
DOI: 10.1039/d0ra09137e
|View full text |Cite
|
Sign up to set email alerts
|

Production of modified sunflowers seed shells for the removal of bisphenol A

Abstract: In this present study, an abundant, available lignocellulosic biomass, sunflower seed shells, SSS, was used as a precursor to prepare an effective eco-adsorbent by treatment with H2SO4 (AC75).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Likewise, in a study by Wang and Zhang et al, magnetic biochar was prepared with excellent reusability [95]. Hayoun et al discovered that the adsorption performance of sunflower seed shells towards BPA could reach 87.81% after treatment with sulfuric acid [96]. These findings collectively highlight how agricultural waste can be repurposed as an effective and sustainable method for removing BPA from the environment.…”
Section: Adsorption Of Bpa By Agricultural Wastesmentioning
confidence: 96%
“…Likewise, in a study by Wang and Zhang et al, magnetic biochar was prepared with excellent reusability [95]. Hayoun et al discovered that the adsorption performance of sunflower seed shells towards BPA could reach 87.81% after treatment with sulfuric acid [96]. These findings collectively highlight how agricultural waste can be repurposed as an effective and sustainable method for removing BPA from the environment.…”
Section: Adsorption Of Bpa By Agricultural Wastesmentioning
confidence: 96%
“…Likewise, in a study byWang and Zhang et al, magnetic biochar was prepared with excellent reusability (Wang and Zhang 2020). Hayoun et al found that sunflower seed shell's adsorption performance towards BPA could reach 87.81% after treatment with sulfuric acid(Hayoun et al 2021). Overall, these studies demonstrate how agricultural waste can be repurposed as an effective and sustainable way to remove BPA from the environment.…”
mentioning
confidence: 89%